Genome-wide identification of the mango CONSTANS (CO) family and functional analysis of two MiCOL9 genes in transgenic Arabidopsis - Liu, Yuan; Luo, Cong; Liang, Rongzhen; Lan, Moying; Yu, Haixia; Guo, Yihang; Chen, Shuquan; Lu, Tingting; Mo, Xiao; He, Xinhua (Frontiers in Plant Science, 2022)
CONSTANS/CONSTANS-like (CO/COL) transcription factors play a vital role in the photoperiodic flowering pathway. However, the biological functions of COL genes in mango are unclear. In this study, we identified 31 COL genes from the ‘Jin Huang’ mango genome and divided them into three groups according to the specific gene structure and protein domain characteristics. These 31 MiCOL genes were heterogeneously distributed on 14 chromosomes. Expression pattern analysis showed that most MiCOL genes were mainly expressed in leaves and stems and during the floral induction period, followed by the floral differentiation period. The expression of COL genes was induced by drought and salt stress, but the expression patterns of different genes were different, which may suggest that MiCOL genes are involved in the abiotic stress response of mango. Under salt and drought conditions, two MiCOL9 genes can improve the resistance of Arabidopsis by improving the scavenging ability of ROS and proline accumulation and reducing the MDA content. Additionally, overexpression of MiCOL9 genes significantly inhibited flowering in transgenic Arabidopsis. This work provides an important foundation for understanding the biological roles of mango COL genes in plant growth, development and stress responses